Identification of Respiratory Burst Oxidase Homolog (Rboh) Family Genes From Pyropia yezoensis and Their Correlation With Archeospore Release - Gui, Tian-Yu; Gao, Da-Hai; Ding, Hong-Chang; Yan, Xing-Hong (Frontiers in Plant Science, 2022)
Reactive oxygen species (ROS) play important regulatory roles in plant growth and development, as well as in cell differentiation and stress responses. Respiratory burst oxidase homolog (RBOH) is the key enzyme in ROS production. So far, the Rboh family genes in Pyropia yezoensis have not been comprehensively characterized, and whether their function was involved in the formation of archeospores is still unknown. In this study, a total of 11 PyRboh genes were identified from the P. yezoensis genome by homology mining. Through phylogenetic analysis, it is suggested that the PyRboh genes were evolutionarily conserved among the lineages of red algae, but a few genes exhibited a species-specific manner. The treatment of P. yezoensis blades with NADPH oxidase inhibitor diphenylene iodonium (DPI) could significantly inhibit the formation of archeospores, suggesting that RBOH may be involved in the formation of archeospores. According to PyRboh gene expression analysis using the P. yezoensis strains with obvious differences in releasing archeospores, it is showed that the expression trends of most genes were consistent, with no significant difference between strains, whereas the expression pattern of the two P. yezoensis-specific genes (PyRbohJ and PyRbohK) was positively correlated with the amount of archeospores. Furthermore, as treatment of blades with allantoin resulted in a significant increase in the release of archeospores, the expression levels of PyRbohJ and PyRbohK were also consistently upregulated, further confirming the relationship between the two genes and archeospore formation. These findings provide insights into the molecular mechanism of P. yezoensis archeospore formation.